Radical-Assisted Formation of Pd Single Atoms or Nanoclusters on Biochar - Xiang, Chong; Liu, Qingya; Shi, Lei; Liu, Zhenyu (Frontiers in Chemistry, 2020)
Supported single atom or nanocluster catalysts have been widely studied due to their excellent catalytic properties. Many methods to prepare such catalysts start with constructing defects on supports, and the main focus is to improve dispersion and stability of the active sites. This paper for the first time reports a radical-assisted method to prepare single atom or nanocluster Pd on a biochar. The char was prepared by pyrolyzing walnut shell at 600°C under N2, and Pd was loaded on the char by impregnating with palladium acetate in toluene under an oxygen-free atmosphere. It is found that there are three types of radicals in the fresh char (F-Char-600), two of them may adsorb/bond with O2 or Pd2+ resulting in decreases in the char's radical concentration. The Pd on F-Char-600 for 24 h impregnation are single atoms (0.1–0.3 nm, 2%) and nanoclusters (0.3–1.2 nm, 98%), which grow larger (0.3–4 nm, 100%) for 84 h impregnation. The Pd on N2 purged O2-adsorbed-char (N-O-Char-600) is much larger in size. The bond between Pd and char is probably C–Pd in F-Char-600 or C–O–Pd in N-O-Char-600.